MODEL PEMBELAJARAN PROJECT BASED LEARNING DENGAN METODE DEMONSTRASI UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR PADA MATERI FLUIDA STATIS - Elisabeth, Najoan Anjelina; Makahinda, Tineke; Mandolang, Aswin Hermanus (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to improve the process and learning outcomes of students on static fluid material using the Project Based Learning Model with the demonstration method. The research design used is a one group pretest posttest design. The sample in the study amounted to 15 students. Data analysis in this study used the help of the SPSS 22 application. Research data were collected using test instruments in the form of essay questions consisting of 5 questions and project assessments based on the rubric used. The results of the project assessment rubric obtained in the learning process were 97% with a very good value category and the project assessment results were 82% with a very good value category. Then the analysis using one sample t test obtained sig. (2-tailed) value is <0.001 where the value obtained is smaller than the value of 0.05 so that H1 is accepted and H0 is rejected. Thus it can be concluded that the project-based learning model with the demonstration method can improve the process and learning outcomes of students.